PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN KESADARAN MEREK SEBAGAI VARIABEL MEDIASI (STUDI PADA KONSUMEN ALFAMART DI KECAMATAN GAYUNGAN, SURABAYA) - ARI, WINDY (Jurnal Ilmu Manajemen (JIM), 2018)
Alfamart is one of convenience store in Indonesia. This Alfamart convenience store, always doing sales promotion to create brand awareness in customers memory. Purpose of this study is to analyze and discuss the effect of sales promotion on purchasing decision with brand awareness as an mediation variable. This research is a causal research that kind of conclusively research. Respondents in this study were women and men aged minimal 19 years old and who buying on Alfamart in Gayungan Districts, Surabaya. The sampling method is non-probability sampling and sampling techniques using judgmental sampling. Data collection techniques used in this study was a questionnaire, while data analyze using path analysis with AMOS program. The results of this study showed that sales promotion has direct effect on brand awareness and purchasing decision, but brand awareness as an mediation don’t has direct effect on purchasing decision. The test results of mediation between dependent and independent variables through intervening variables not proved. Keywords: Sales Promotion, Brand Awareness, Purchasing Decision